1995
DOI: 10.1163/156856195x00239
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser-induced photochemical modification and adhesion improvement of a fluororesin surface

Abstract: Modification of a selective area of a fluororesin surface was accomplished by using ArF excimer laser radiation and a boron complex with oleophilic or hydrophilic functional groups. The chemical stability of fluororesin is attributed to the presence of C-F bonds. The F atoms were abstracted by B atoms selectively from the area irradiated with excimer laser radiation and were replaced with the desired functional groups. In this modification, B(CH3)3 and B(OH)3 were used: a boron compound with methyl groups to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…In addition, this technique can be performed with safety and in the open air, with no environmental disruption and no need for vacuum system. 12 In conclusion, copper nuclei for area-selective deposition onto fluorocarbon-resin surface were formed using an ArF excimer laser and CuSO 4 aqueous solution. The ArF excimer laser photons were able to induce the defluorination effectively using the hydrogen atoms which were photodissociated from the water of the CuSO 4 aqueous solution.…”
Section: Area-selective Nucleation Of Copper On Fluorocarbon-resin Sumentioning
confidence: 99%
“…In addition, this technique can be performed with safety and in the open air, with no environmental disruption and no need for vacuum system. 12 In conclusion, copper nuclei for area-selective deposition onto fluorocarbon-resin surface were formed using an ArF excimer laser and CuSO 4 aqueous solution. The ArF excimer laser photons were able to induce the defluorination effectively using the hydrogen atoms which were photodissociated from the water of the CuSO 4 aqueous solution.…”
Section: Area-selective Nucleation Of Copper On Fluorocarbon-resin Sumentioning
confidence: 99%
“…With laser treatment in reactive atmosphere (e.g., hydrazine [100,101]) or under various liquids (e.g., B(CH 3 ) 3 [102,103]), the F--C bonds on the surface can be broken, CH 3 radicals or amino groups can be incorporated, allowing to apply a coating after laser treatment. This surface modification takes place without detectable ablation.…”
Section: Fluoropolymersmentioning
confidence: 99%
“…We have photo-chemically incorporated both hydrophilic and hydrophobic groups, as well as metal atoms, on the PTFE surface by ArF excimer laser irradiation, without any physical damage [16][17][18][19][20][21][22][23][24]. In our previous studies, we incorporated desired functional groups or metal atoms onto the polymer surface using an excimer laser to generate a hydrophilic or hydrophobic surface and found that especially for PTFE, B, Al and H atoms were effective in defluorinating [16,17,21].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we incorporated desired functional groups or metal atoms onto the polymer surface using an excimer laser to generate a hydrophilic or hydrophobic surface and found that especially for PTFE, B, Al and H atoms were effective in defluorinating [16,17,21]. Having studied the compatibility between the defluorinating atoms and a living body extensively, it was found that when using B and Al, their compounds remained on the modified surface and became impurities to cause rejections; however, no rejection occurred on the hydrophilic PTFE modified with H, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation